Collecting wood core samples from Macassar ebony (Diospyros celebica Bakh.) for multi-purpose analysis using pickering punch - Iskandar Zulkarnaen Siregar; Muhammad Majiidu; Fifi Gus Dwiyanti; Essy Harnelly; Ratih Damayanti; Lina Karlinasari; Mohamad Rafi; Dewi Anggraini Septaningsih; Meaghan Parker-Forney (MethodsX, 2022)
Sample collection activities for a study of population genetics across the natural distribution of targeted tree species require a lot of resources, mainly if repeated field visits are necessary. Conventionally, population genetic studies use good sample material like leaves. In addition, cambium or small pieces of fresh wood can be used to replace leaf samples. Currently, restrictions from the permit regulation have caused only a limited number of samples that can be collected. Therefore, efficient use of samples must be designed to maximize their uses for research. Due to the small amount of successfully sampled materials, hence there are limitations to extend their uses for other analyses and are often sufficient only for genetic analysis. Therefore, innovation in sampling methods using pickering punch (https://www.agroisolab.com/pickering-punch) to collect ebony wood cores in this study is required to cover multi-analyses not only limited to genetics but also for other analyses such as isotopes, near-infrared spectroscopy (NIRs), anatomy, and chemical compounds. • Pickering punch is recommended for efficient wood core sample collection from ebony standing trees. • 323 wood core samples were successfully collected from 16 natural populations across Celebes (Sulawesi). • Multi-analyses studies on sampled wood cores are possible for ebony wood identification (e.g., species and origin/provenance).